Design of Decision Support System Selection of Beach Tourism Object in GunungKidul using Fuzzy AHP Method - Istianto, Yudi; Sugiantoro, Bambang (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
The tourism industry is currently one of the important assessments for a certain region. Gunungkidul has a lot of of beach tourism potentials until visitors are confused to choose the right beach. The purpose of this research is to analyze and apply Fuzzy Analytical Hierarchy Process method in calculating the selection of beach tourism object in Gunungkidul with eight main criteria into a website.Multi Criteria Decision Making (MCDM) is a decision-making method to establish the best alternative of a number of alternatives based on several criteria that will be considered. One method of MCDM is the Fuzzy Analytical Hierarchy Process method. Fuzzy Analytical Hierarchy Process is a method of developing Analytical Hierarchy Process (AHP), which can describe unclear decisions and minimize uncertainty on AHP. Fuzzy approach, especially triangular fuzzy number to AHP scale, is expected to minimize uncertainty so that expected result was obtained more accurately.The decision support system for choosing a beach resort in Gunungkidul has been successfully built by applying the Fuzzy Analytical Hierarchy Process method. The calculation of Fuzzy Analytical Hierarchy Process method with the same computer result with manual calculation. The testing system was done using Black Box method by testing Alpha and Betha. From the results of system testing, it was known that the average result of the overall function score was 104 which was on rating scale 97.51 - 120 (Very Good).